IN SEARCH OF CONTEXTUAL AND HUMANISTIC SOUTHEAST ASIAN LITERATURE IN ENGLISH - Novita Dewi (Celt: A Journal of Culture, English Language Teaching & Literature, 2014)
English literature studies in Indonesia has to undergo a paradigm shift, given the demographic change of users and providers of English, to say nothing of the growing interests in Asian literature written in and/or translated into English. Mindful of our postcolonial experiences in today's cultural and political context, the use of more literary pieces from Southeast Asian countries in English Literature studies is all the more important. This paper locates Southeast Asian literature within the development of English as a Lingua Franca. Characteristic of our postmodern age is the recognition of people as human; and, in this case, Asian people as individuals, multilingual and multicultural subjects. As such, reading and evaluating works from the region may help develop a deeper understanding when defining our own place in relation to other people. It is through engaging in contextual and humanistic literary experiences that we measure and value the connection between literature and life.